Malocclusions, pathologic tooth migration, and the need for orthodontic treatment in subjects with stage III–IV periodontitis. A cross-sectional study - Zasčiurinskienė, Eglė; Rastokaitė, Liveta; Lindsten, Rune; Basevičienė, Nomeda; Šidlauskas, Antanas (European journal of orthodontics, 2023)
Summary Background Literature is scarce on malocclusion prevalence and orthodontic treatment need (OTN) in subjects with stage III–IV periodontitis. Study aims were to assess prevalence of primary and secondary malocclusions in subjects with stage III–IV periodontitis and OTN based on pathologic tooth migration (PTM) and occlusal trauma of anterior teeth (AT). Subjects and methods One hundred and twenty-one subjects with stage III–IV periodontitis were examined. A comprehensive periodontal–orthodontic examination was performed. Exclusion criteria: age <30 years, removable prosthetics, uncontrolled diabetes, pregnancy/lactation, and oncologic disease. Results Class II malocclusion was found in 49.6% (Class II div 1—20.7%, Class II div 2—9.9%, subdivision Class II—19.0%), Class I—31.4%, Class III—10.7%, no malocclusion—8.3% of subjects. PTM was observed in 74.4% of maxillary and 60.3% of mandibular AT. Spacing and extrusion were the main types of PTM of AT. Odds ratio for PTM of maxillary AT was 9.3 in cases with >30% of sites with clinical attachment loss ≥5 mm (P = 0.001). Spacing of maxillary AT was influenced by periodontitis, Class III malocclusion, and lost teeth. Tongue habit had impact on spacing of mandibular AT. Dental Health Component of Index of Orthodontic Treatment Need yielded that OTN was found in >50% and OTN due PTM, occlusal trauma and impaired function in 66.1% of subjects. Conclusions The most prevalent malocclusion was Class II. Spacing and extrusion were prevalent types of PTM of AT. OTN was found in more than half of the subjects. The study highlights the need for preventive measures for PTM in subjects with stage III–IV periodontitis.